2009
DOI: 10.1111/j.1365-2958.2009.06863.x
|View full text |Cite
|
Sign up to set email alerts
|

Membrane transport proteins of the malaria parasite

Abstract: SummaryThe malaria parasite-infected erythrocyte is a multicompartment structure, incorporating numerous different membrane systems. The movement of nutrients, metabolites and inorganic ions into and out of the intraerythrocytic parasite, as well as between subcellular compartments within the parasite, is mediated by transporters and channels -integral membrane proteins that facilitate the movement of solutes across the membrane bilayer. Proteins of this type also play a key role in antimalarial drug resistanc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
82
1

Year Published

2012
2012
2017
2017

Publication Types

Select...
5
4

Relationship

1
8

Authors

Journals

citations
Cited by 81 publications
(85 citation statements)
references
References 88 publications
(163 reference statements)
2
82
1
Order By: Relevance
“…The localization of both enzymes in the cytoplasmic compartment (Fig. 6), as aldolase and other enzymes involved in the metabolism of carbohydrates (68), agrees well with the identification of a putative GDP-Fuc transporter in the P. falciparum endoplasmic reticulum/Golgi apparatus (69), where N-and O-glycosylation processes occur. The location and function of a putative fucosecontaining glycan in P. falciparum remain enigmatic, and biosynthetic labeling with tritiated fucose is not feasible, because there is no prominent GDP-Fuc salvage pathway in the parasite, and/or hexose transporters do not efficiently take up fucose (Fig.…”
Section: Discussionsupporting
confidence: 57%
“…The localization of both enzymes in the cytoplasmic compartment (Fig. 6), as aldolase and other enzymes involved in the metabolism of carbohydrates (68), agrees well with the identification of a putative GDP-Fuc transporter in the P. falciparum endoplasmic reticulum/Golgi apparatus (69), where N-and O-glycosylation processes occur. The location and function of a putative fucosecontaining glycan in P. falciparum remain enigmatic, and biosynthetic labeling with tritiated fucose is not feasible, because there is no prominent GDP-Fuc salvage pathway in the parasite, and/or hexose transporters do not efficiently take up fucose (Fig.…”
Section: Discussionsupporting
confidence: 57%
“…A higher uptake of HEDICINs 8, as compared to HECINs 9, could arise from: a) a more efficient transport by passive diffusion, as HEDICINs are more lipophilic than HECINs; globally, HEDICINs and HECINs have similar acidebase properties (average estimated pKa w 4 for deprotonation of the quinolinic nitrogen), but differ by almost two units in their estimated logP values (4.2 < logP < 5.1 for HECINs; 5.8 < log P < 7.9 for HEDICINs; cf. Table 1) [33], with the most lipophilic, 8c, being also the most active anti-plasmodial; amino acid and dipeptide esters are known to cross cell membranes by passive diffusion [38], so it is possible that the presence of the dipeptide spacer in HEDICINs augments cell permeation of these compounds by such process; b) recognition of the dipeptide motif by specific transporters from the P. falciparum ABC transporter super-family, many of which have been taken as putative drug transporting proteins [39] and found to be directly implicated in drugresistance mechanisms [40,41]; c) increased permeability of dipeptide derivatives due to the new permeation pathways created in P. falciparum-infected RBCs to promote uptake of nutrients such as sugars or nucleosides [42], as well as amino acids and oligopeptides [31]; II. Alternatively, a difference in the respective mechanism of action (MOA) may be operating in addition, or in alternative, to a difference in uptake of HEDICINs versus HECINs: a) due to their dipeptide moiety, HEDICINs might be able to inhibit plasmodial cytosolic proteases like aminopeptidases PfA-M1 and PfA-M17, which function in regulating the intracellular pool of amino acids required for parasite growth and development inside the red blood cell [43,44]; b) HEDICINs anti-plasmodial activity could otherwise be related to the cinnamoyl moiety, as it has been shown that cinnamic acid derivatives inhibit the growth of intraerythrocytic P. falciparum in culture by inhibiting monocarboxylate (e.g.…”
Section: Fukui Indices Of the Vinyl Carbons In Hecinsmentioning
confidence: 99%
“…ABC transporters play a key role in multidrug resistance (MDR), both in human cancer cells and in pathogenic microbes 5,6 . The P. falciparum genome encodes 11 putative ABC transporter proteins 7 . Thus far, Plasmodium ABC proteins have been studied in the context of their prominent roles in conferring drug resistance.…”
mentioning
confidence: 99%